1994
DOI: 10.1182/blood.v84.5.1508.bloodjournal8451508
|View full text |Cite
|
Sign up to set email alerts
|

Stromal cell lines derived from LP-BM5 murine leukemia virus-infected long-term bone marrow cultures impair hematopoiesis in vitro

Abstract: Murine acquired immunodeficiency syndrome (MAIDS) induced by defective LP-BM5 murine leukemia virus is a disease with many similarities to human AIDS. Previous studies indicated that the depressed hematopoiesis observed in LP-BM5-infected marrow cultures may be attributable to a defect of hematopoietic stroma. We report here the generation of permanent stromal cell lines from noninfected and LP-BM5-infected marrow cultures. Retrovirus infection was confirmed by polymerase chain reaction for viral genome. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Many retroviruses can cause hematopoietic abnormalities, including HIV in humans (Maciejewski et al, 1994;Re et al, 1994), SIV in monkeys (Mandell et al, 1995;Watanabe et al, 1990), FIV in cats (Linenberger and Abkowitz, 1995), and MuLV in mice (Li and Fan, 1990;Tse et al, 1994). Here we report that retroviral infection of rats also caused bone marrow alterations.…”
Section: Discussionsupporting
confidence: 50%
“…Many retroviruses can cause hematopoietic abnormalities, including HIV in humans (Maciejewski et al, 1994;Re et al, 1994), SIV in monkeys (Mandell et al, 1995;Watanabe et al, 1990), FIV in cats (Linenberger and Abkowitz, 1995), and MuLV in mice (Li and Fan, 1990;Tse et al, 1994). Here we report that retroviral infection of rats also caused bone marrow alterations.…”
Section: Discussionsupporting
confidence: 50%
“…Tse et al (1993) demonstrated that growth of haemopoietic progenitors is impaired in long-term bone marrow cultures (LTBMC) of MAIDS mice. More recently, they demonstrated defective cytokine production in LP-BM5-infected established bone marrow stromal cell lines (Tse et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The production of cytokines was estimated using reverse transcription-polymerase chain reaction (RT-PCR) assays with previously defined primers [34][35][36][37][38]. Amplifications (30 to 35 times) were performed according to established protocols and using known controls [34][35][36][37][38].…”
Section: Cytokine Productionmentioning
confidence: 99%